Evaluation of Pseudomonas fluorescens isolates for the management of Fusarium oxysporum f.sp. lycopersici and Rhizoctonia solani responsible for causing wilt complex in tomato - V.K. RAZDAN, STANZIN DORJEY, VISHAL GUPTA* and (Indian Phytopathology, 2017)
Twenty-five isolates of Pseudomonas fluorescens were isolated from healthy plants of tomato on Kings’B medium, for exploring their bio-efficacy potential against Fusarium oxysporum f.sp. lycopersici and Rhizoctonia solani, responsible for wilt complex disease. Out of all, six isolates (I-7, I-15, I-18, I-23, I-24 and I-25) significantly inhibited the growth of both fungal pathogens under laboratory conditions. Under green house conditions, bacterization of tomato seeds with these six isolates of P. fluorescens in pathogen infested soil significantly reduced the incidence of disease caused by F. oxysporum f.sp. lycopersici and R. solani, with maximum (12.50 and 10.41%) by isolate I-23, and simultaneously increased the plant growth parameters. Application of isolate I-23 also resulted in maximum per cent germination, shoot length and root length of 80.00 and 77.50 per cent and 54 and 38 cm and 16.27 and 11.97 cm, respectively as compared to their untreated control.